(untitled) (Journal of Advanced Veterinary and Animal Research, 2015)
This study was undertaken for isolation, identification and determination of antibiogram profile of Aeromonas hydrophila in farm raised fresh water prawn (Macrobrachium rosenbergii) on five commercial ghers. Fresh water prawns (n=25) were collected from five ghers located at Satkhira, Bagerhat and Khulna districts of Bangladesh. Brain (n=25), muscle (n=25) and intestine (n=25) samples were collected aseptically from fresh water prawn and inoculated into alkaline peptone (APW) water for enrichment at 37 ? for 8 h. Enriched cultured was streaked into Thiosulfate Citrate Bile Salt Sucrose (TCBS) agar to isolate bacteria. Bacteria were identified by cultural, Gram staining, biochemical properties and polymerase chain reaction (PCR) assay. The antibiogram profiles of bacteria were investigated against 5 commonly used antibiotics (Gentamicin, Cefalexin, Ampicillin, Azithromycin and Ciprofloxacin) by disc diffusion method. Thirteen A. hydrophila isolates were identified and the prevalence of the A. hydrophila in fresh water prawn was 17.33%. All 13 (100%) isolates were sensitive to Ciprofloxacin, Gentamicin, Azithromycin and resistant to Ampicillin and Cefalexin. The results of this study indicate that farm raised fresh water prawn harbor multidrug resistant A. hydrophila which might causes public health problem if enter into human food chain. http://dx.doi.org/10.5455/javar.2015.b120